Methods of Teaching English in Primary School - Kochkorova Zulfizar Abduxamid qizi; Pulatjonova Gulxumor Nuriddinovna (Journal of Innovation in Education and Social Research, 2023)
An overview on how to teach English quickly and easily in elementary school is dealt with in this article. By this article, we explore meaningful and fun ways of teaching English in primary school.